Pengendalian Kualitas Menggunakan Six Sigma untuk Mengurangi Jumlah Defect pada Produk Maswite Masterbatch - Mochamad Yusuf Bachruddin; Rukmana, Asep Nana; Bachtiar, Iyan (UNISBA Press, 2024)
Abstract. PT Masolikalerindo Perkasa is a company engaged in the color plastic material industry which was established in 1995. The product produced by PT Masolikalerindo Perkasa is called Maswite Masterbatch in the form of plastic seeds. This research was conducted in the Maswite Masterbatch production section. Based on the results of preliminary observations in the field, information was obtained that there were problems in the company in controlling its quality. The problems experienced by the company are in the form of product defects. Defects in Maswite Masterbatch products include dusty defects, small size defects, and tail defects. The average percentage of defects is 5.97% where this figure exceeds the tolerance limit for defects set by the company which is 3%. One solution to overcome the problems faced is the six sigma method. The six sigma method has five stages, namely Define, Measure, Analyze, Improve and Control (DMAIC). The results of making the Pareto diagram showed that the highest type of defect was dusty. Furthermore, the calculation of Defect per Million Opportunity (DPMO) for six months obtained a DPMO value of 19,903 and a sigma level of 2.33. The FMEA stage is carried out by determining the level of severity, occurrence, and detection as well as determining the RPN. The highest RPN value of 378 is found in the unstable raw material warehouse temperature factor. The results of implementing the six sigma method are carrying out maintenance and checking once a month, carrying out the process of monitoring the mixing process at every shift change, and providing appropriate room temperature settings with the proposed purchase of air conditioning and a thermometer to keep the temperature stable. Abstrak. PT. Masolikalerindo Perkasa merupakan perusahaan yang bergerak di bidang industri bahan plastik warna yang didirikan pada tahun 1995. Produk yang dihasilkan oleh PT Masolikalerindo Perkasa dinamakan Maswite Masterbatch yang berupa biji plastik. Penelitian ini dilakukan di bagian produksi Maswite Masterbatch. Berdasarkan hasil pengamatan awal di lapangan, diperoleh informasi bahwa terdapat permasalahan pada perusahaan dalam pengendalian kualitasnya. Permasalahan yang dialami oleh perusahaan berupa adanya defect pada produk. Defect pada produk Maswite Masterbatch di antaranya defect berdebu, defect ukuran kecil, dan defect berekor. Rata-rata persentase defect yaitu sebesar 5,97% dimana angka tersebut melebihi dari batas toleransi terhadap defect yang ditetapkan oleh perusahaan yaitu sebesar 3%. Salah satu solusi untuk mengatasi permasalahan yang dihadapi adalah metode six sigma. Hasil pembuatan diagram Pareto diperoleh jenis defect tertinggi adalah berdebu. Selanjutnya dilakukan perhitungan Defect Per Million Opportunity (DPMO) selama enam bulan diperoleh nilai DPMO sebesar 19.903 dan level sigma 2,33. Tahapan FMEA dilakukan dengan penentuan severity, occurrence, dan detection serta penentuan RPN. Nilai RPN tertinggi sebesar 378 terdapat pada faktor suhu gudang ruangan bahan baku tidak stabil. Hasil dari penerapan metode six sigma yaitu melakukan perawatan dan pengecekan setiap 1 bulan sekali, melakukan proses pengawasan proses mixing setiap pergantian shift, dan menyediakan ketetapan suhu ruangan yang tepat dengan usulan pembelian AC serta termometer untuk menjaga suhu tetap stabil.